Date fruit processing waste and approaches to its valorization: A review. (November 2021) - Oladzad, Sepideh; Fallah, Narges; Mahboubi, Amir; Afsham, Neda; Taherzadeh, Mohammad J.
Graphical abstract: Highlights: Characterizing and valorizing date processing waste are reviewed. Date processing waste (DPC) are rich in chemicals and nutrients. DPC have the potential to be used as a bioeconomy feedstock. We still need lab and pilot studies before DPC is valorized. Characterization of date processing waste is rarely considered. Abstract: In the Middle East and North Africa, dates are a traditional and economically valuable crop, playing an essential role in people's daily diets. Date fruit production and related processing industry generate a large quantity of waste; for illustration, the date juicing industry produces roughly 17–28% Date press cake (DPC), which is mainly discarded in open lands and drains. Considering the generation volume and the nutrient content of DPC, this organic by-product stream can be valorized through the production of a wide range of products with a great market appeal, such as volatile fatty acids, activated carbon, organic acids, etc. To provide an insight into the feasibility of the application DPC as a green precursor for various chemical and biological processes, the chemical and nutritional composition of dates and DPC, an overview of the date processing industries, and common practices conducted for DPC valorization addressed and thoroughly discussed, in this review.